Pengaruh Promosi dan Lokasi terhadap Keputusan Pembelian Tenun Ikat Sanggar KWT Eban Watan di Desa Ian Tena, Kabupaten Sikka - Yosef Kalansius Masong; Walter Obon; Dimas Realino (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2025)
This research was motivated by problem of purchasing decisions (Eban Watan Women’s Studio of Ian Tena Village, Sikka Regency). This study aimed to; (1) figure out the description of purcasing decisions, promotion, and location of the Eban Watan Farmer women’s groph studio; (2) analize promotion and lokation ond procasing both partially and simultaneously. The population in this study were all consumers who made procases of ikat weaving at the Eban Watan Farmwr Women’s Group Studio Ian Tena Village with a sampling of 70 people using The Non-Probability Sampling method which mean that the elements in the population did not heve an inherent probability of being slected as a subject person. Data were collected through questionnaires and analized using descritive and inferential statistical methods, namely multyple linear regrenssion. Hypothesis testing was done through F and t-tests. Descritive analysis showed that the varyables of buyer decisions, promotions and locations were categorized as good. The statical results of the t-test sha effect ond purcahasing decisions. The result of the F test showed that simultaneously all independent variables had a significant effect on purchasing decisions. Tha coefficient of determination that the contributiont of the promotion variable and the location variable to the purcases decision of the weaving studio Eban Watan Ian Tena Village, Sikka Regency was 49,9%, while it was infulenced by outher factors outside the research variables.